2009
DOI: 10.1016/j.crohns.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Nkx2-3 polymorphism with Crohn's disease and expression of Nkx2-3 is up-regulated in B cell lines and intestinal tissues with Crohn's disease

Abstract: Nkx2-3 is genetically associated with CD and is up-regulated in CD, suggesting that Nkx2-3 is involved in the pathogenesis of CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Since our studies showed rs2542151 and rs2542152 were associated with CD but not UC, there may be a possible connection between the association of the two SNPs with PTPN2 up-regulation in CD. NKX2-3 is associated with IBD and up-regulated in CD patients [10]. We found that expression of NKX2-3 was increased in B cells and intestinal tissues from CD patients, and expression of PTPN2 was decreased in NKX2-3 knockdown human cells.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Since our studies showed rs2542151 and rs2542152 were associated with CD but not UC, there may be a possible connection between the association of the two SNPs with PTPN2 up-regulation in CD. NKX2-3 is associated with IBD and up-regulated in CD patients [10]. We found that expression of NKX2-3 was increased in B cells and intestinal tissues from CD patients, and expression of PTPN2 was decreased in NKX2-3 knockdown human cells.…”
Section: Discussionmentioning
confidence: 64%
“…NKX2-3 (NK2 transcription factor related, locus 3) is an IBD-associated intestinal transcription factor [1,2] with increased levels of mRNA expression in CD patients [10]. Our cDNA microarray data showed that PTPN2 expression is down-regulated following knockdown of NKX2-3 in B cells from IBD patients [11,12] and human intestinal microvascular endothelial cells (HIMEC) [13].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations